Hungarian Monitoring, 23 February 1990 . [Magyar rádiófigyelő], 1990. február 23 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Baltic reports on the situations in Estonia and Lithuania - Growing tension in Ukraine - Romanian interim national unity council in session - Sino-Soviet troop withdrawals agreement - German unity - New government in Sweden Domestic Affairs: - László Paskai's trip to Transylvania - Horn on the disintegration of the USSR - Workers' Militia in Székesfehérvár - Cleansing downtown Budapest of foreign black marketeers - Elections: Alliance of Free Democrats (SZDSZ) rally, Hungarian Democratic Forum (MDF) statement, election programs Economy: - Difficulties in Hungarian-Soviet trade relations; stopping socialist exports - Interpellation on taxing interest - Hearing in the case of Csepel Car Factory vs. Ikarusz Külpolitika: - Baltikumi tudósítás az észt és litván helyzetről - Ukrajnában is feszültté vált a helyzet - A román ideiglenes nemzeti egységtanács ülése - Szovjet-kínai csapat visszavonási megegyezés - A német egység kérdése - A svéd kormányalakításról Belpolitika: - Paskai László erdélyi útja - Horn a felbomlóban levő Szovjetunióról - Munkásőrség Székesfehérváron - A belváros megtisztítása a külföldi feketézőktől - Választás: SZDSZ nagygyűlés, MDF nyilatkozat, választási műsorok Gazdaság: - Magyar-szovjet kereskedelmi kapcsolatok nehézségei; a szocialista export leállítása - Interpelláció a kamatadóról - Csepel Autógyár kontra Ikarus gazdasági per tárgyalása